Brine shrimp lethality and phytochemical determination of aqueous extracts of Senna singueana, Musa paradisiaca, and Ziziphus mucronata in Malawi. (Journal of Basic and Applied Research in Biomedicine, 2015)
Traditional medicine is still practiced in different parts of the world; with traditional healers as powerful and important members of the society. Senna singueana, Musa paradisiaca, and Ziziphus mucronata plants are commonly used by traditional healers to treat different ailments in Malawi. There is need to conduct a scientific lethality evaluation of these plants to assess their fitness for human consumption as traditional medicine. The aqueous extraction of leaves and roots of Senna singuenna, Musa paradisiaca, and Ziziphus mucronata mimicking similar environment as provided by traditional healers, afforded dry extracts. Brine shrimp toxicity testing was done following a modified procedure to determine in-vitro cytotoxicity for the herbal extracts. The findings suggest that the leaves and roots tested exhibited concentration dependent toxicity against brine shrimps with the exception of Ziziphus mucronata roots which showed some toxicity to brine shrimps after 48 hours of incubation. Brine shrimp results suggest that the plant extracts were virtually non-toxic on the shrimps save Senna singueana leaves, Ziziphus mucronata roots, which exhibited low toxicity on brine shrimps after 48 hours of incubation. The observed toxic activity for Ziziphus mucronata roots may be due to the presence of well documented cytotoxic compounds such as Swertish and Apigenine glucoside.